2017
DOI: 10.1038/s41598-017-10434-7
|View full text |Cite
|
Sign up to set email alerts
|

The extraordinary variation of the organellar genomes of the Aneura pinguis revealed advanced cryptic speciation of the early land plants

Abstract: Aneura pinguis is known as a species complex with several morphologically indiscernible species, which are often reproductively isolated from each other and show distinguishable genetic differences. Genetic dissimilarity of cryptic species may be detected by genomes comparison. This study presents the first complete sequences of chloroplast and mitochondrial genomes of six cryptic species of A. pinguis complex: A. pinguis A, B, C, E, F, J. These genomes have been compared to each other in order to reconstruct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
63
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(71 citation statements)
references
References 67 publications
8
63
0
Order By: Relevance
“…These remarkable improvements include that liverworts were strongly supported as sister to mosses in recent phylogenomic studies (Wickett et al, 2014;Puttick et al, 2018;de Sousa et al, 2018) than the alternative hypothesis of this group as the earliest lineage of land plants (Qiu et al, 1998(Qiu et al, , 2006. These findings, consistent with those of the first chloroplast phylogenomic analysis (Nishiyama et al, 2004), not only provide new insights into the deepest diverging events of land plants, but also enable us to reappraise hypotheses on the evolution of key innovative morphological characters (e.g. stomata) and evolutionary events, based-hitherto--on early land plant fossils Puttick et al, 2018).…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…These remarkable improvements include that liverworts were strongly supported as sister to mosses in recent phylogenomic studies (Wickett et al, 2014;Puttick et al, 2018;de Sousa et al, 2018) than the alternative hypothesis of this group as the earliest lineage of land plants (Qiu et al, 1998(Qiu et al, , 2006. These findings, consistent with those of the first chloroplast phylogenomic analysis (Nishiyama et al, 2004), not only provide new insights into the deepest diverging events of land plants, but also enable us to reappraise hypotheses on the evolution of key innovative morphological characters (e.g. stomata) and evolutionary events, based-hitherto--on early land plant fossils Puttick et al, 2018).…”
Section: Introductionsupporting
confidence: 69%
“…0.48% of liverwort species diversity), representing 33 families (42% of family diversity) and 13 orders (87% of order diversity). The chloroplast genome data for 31 liverwort species were newly generated as part of our project on the diversity of liverwort chloroplast genomes (see, also, Yu et al., unpublished) and four were extracted from previously published studies: Aneura pinguis (Myszczyński et al., ), Marchantia polymorpha (Ohyama et al., ), Apopellia endiviifolia (Grosche et al., ) and Ptilidium pulcherrimum (Forrest et al., ). Specimen information and accession numbers are listed in Table .…”
Section: Methodsmentioning
confidence: 99%
“…As a consequence, the evolutionary history of plastid genomes during the colonization of land by plants is still poorly understood. The few available bryophyte plastomes suggest evolutionary conservatism of the genome structures, especially among liverworts (Wickett et al, 2008;Forrest et al, 2011;Wicke et al, 2011;Grosche et al, 2012;Myszczyński et al, 2017), although some gene deletions were found in the nonphotosynthetic liverwort A. mirabilis (Wickett et al, 2008;Myszczyński et al, 2017). Thus, liverworts may diverge from vascular plants and even mosses by the absence of evidence supporting major structural reorganization as a major process in the plastid genome evolution (Wicke et al, 2011;Mower & Vickrey, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, four SNPs near to 3' end of psbA gene are surrounded by 14 bp IRs. Number of sequence variations in N. alba reflects low level of genetic diversity in comparison to other studies (Young et al 2011;Myszczy nski et al 2017).…”
mentioning
confidence: 57%